ANALISIS PENGARUH DISPOSISI MATEMATIS PADA MATAKULIAH TEORI BILANGAN MENGGUNAKAN MODEL PBL SETTING STAD - Konstantinus Denny Pareira Meke; Maria Trisna Sero Wondo; Sofia Sa'o (Program Studi Pendidikan Matematika, 2022)
This study aims to analyze students' mathematical dispositions using the PBL model setting STAD. The sample in this study was the second-semester students of the Mathematics Education Study Program at the University of Flores for the academic year 2020/2021 as many as 20 people. This study uses survey and correlational methods. The research instrument used a non-test instrument, namely a questionnaire composed of 27 statements based on indicators of mathematical disposition, namely: 1) self-confidence, 2) self-efficacy, 3) curiosity, 4) happiness to do assignments, diligent and diligence, 5) flexible, and 6) reflective. The results showed that learning number theory using the PBL model setting STAD in second-semester students of the University of Flores' mathematics education study program for the 2020/2021 academic year got a positive response were on average students had a high mathematical disposition attitude indicator, namely 68.5%.